High Latitude Corals Tolerate Severe Cold Spell - Tuckett, Chenae A.; Wernberg, Thomas (Frontiers in Marine Science, 2018)
Climatically extreme weather events often drive long-term ecological responses of ecosystems. By disrupting the important symbiosis with zooxanthellae, Marine Cold Spells (MCS) can cause bleaching and mortality in tropical and subtropical scleractinian corals. Here we report on the effects of a severe MCS on high latitude corals, where we expected to find bleaching and mortality. The MCS took place off the coast of Perth (32°S), Western Australia in 2016. Bleaching was assessed before (2014) and after (2017) the MCS from surveys of permanent plots, and with timed bleaching searches. Temperature data was recorded with in situ loggers. During the MCS temperatures dipped to the coldest recorded in ten years (15.3°C) and periods of <17°C lasted for up to 19 days. Only 4.3% of the surveyed coral colonies showed signs of bleaching. Bleaching was observed in 8 species where those most affected were Plesiastrea versipora and Montipora mollis. These findings suggest that high latitude corals in this area are tolerant of cold stress and are not persisting near a lethal temperature minimum. It has not been established whether other environmental conditions are limiting these species, and if so, what the implications are for coral performance on these reefs in a warmer future.